Crystal morphology, crystallization behavior, polymorphic crystalline structure and thermal stability of poly(1, 4-butylene adipate) modulated by a oxalamide derivative nucleating agent. (October 2017) - Yang, Jinjun; Liang, Rong; Kong, Rui; Chen, Yichun; Wang, Xiaomin; Yin, Jing; Wan, Jiping; Wang, Xiaoli; Bi, Chengliang
Abstract: In this work, a oxalamide derivative, N 1, N 1′ -(ethane-1, 2-diyl)bis( N 2 -phenyloxalamide) (EDPO) was synthesized successfully to prepare the poly(1, 4-butylene adipate) PBA/EDPO composite. The EDPO first crystallized into the rod-like (shish) and induced the PBA crystal aligned perpendicularly to the EDPO rod axis. As an effective nucleating agent, the EDPO highly increased the crystallization rate and shortened the crystallization time of the PBA. The EDPO not only facilitated the formation of the PBA α -crystal and modulated the polymorphic crystalline structure of the PBA, but also accelerated the β -to- α phase transition of the PBA. Upon the extremely low (such as 0.1%) weight fraction of the EDPO, the thermal stability of the PBA increased pronouncedly. The mechanisms on the nucleation and growth of the PBA, the preferential formation of the α -crystal, accelerated phase transition and enhanced thermal stability of the PBA were also proposed and discussed.